Investigation of maximum erosion zone in the horizontal 90Â° elbow - Khan, R. (Springer Science and Business Media Deutschland GmbH, 2020)
Sand transportation within flow devices causes major problems for the hydrocarbon production industry and entails crucial material removal from pipelines and leads to failure and malfunction of the piping system. The 90Â° elbow configuration is an indispensable flow changing device used to redirect the flow direction in hydrocarbon and mineral processing industries. This paper highlights a comprehensive approach to quantify erosion in 90Â° elbow configuration ensues from fine particle transportation with the carrier fluid. A multilayer paint modeling (MPM) technique and computational fluid dynamics (CFD) are adopted to map the erosion distribution inside the elbow under liquidâsolid flow in a flow loop setup. The experiments for horizontal-to-horizontal (HâH) orientation elbow with 50.8Â mm inner diameter are performed with fine sand of 50Â Î¼m size entertains in a carrier fluid at 3Â m/s. The high erosion zones have been located near the outlet of the 90Â° elbow under fine particle impact with a maximum erosion rate of 1.82Â mm/year in horizontalâhorizontal (HâH) oriented elbow. Â© Springer Nature Singapore Pte Ltd 2020.